Development of Digital Teaching Materials Based on Local Wisdom (Batu Lingga) in Improving Fifth Grade of Elementary School Cultural Literacy - SITI MALIHAH; Dase Erwin Juansah; yuyu yuhana (Universitas Majalengka, 2024)
Abstract This research is motivated by 1) Lack of use of interesting teaching materials in the science and science learning process; 2) There is no use of teaching materials that utilize local regional wisdom as an innovative and interesting learning resource at SDN Baros 3; 3) Lack of student interest in learning science and science; 4) The results of class V science and science learning at SDN Baros 3 are still not optimal. This research aims to describe and analyze the stages of development, feasibility, effectiveness, as well as describe and analyze students' responses to digital teaching materials based on local wisdom (Batu Lingga) in the science and sciences subject of cultural heritage material in class V UPT SDN Baros 3. This research uses ADDIE Research and Development model method which includes five stages including analysis, design, development, implementation, and evaluation. The results of this research show that 1) the feasibility test by material experts is included in the